Challenges in Early Childhood Care & Education (ECCE) in public sector schools of South Punjab: A Qualitative Study - Pirzada, Gouhar (UMT Education Review, 2025)
Despite ECCE serving as a main support for children’s development, its application in public schools in South Punjab did not work very well due to various issues. The study conducted qualitative research into the delivery barriers of ECCE programs through the feedback of 14 educators and administrators from six districts. Findings revealed three critical issues: (1) Long delays in how policies were carried out, (2) A lack of trained teachers in early childhood education, and (3) Difficulties for parents to be involved because of their low economic status. The research suggested that to overcome these problems, integrated approaches, for example, community-based information campaigns and teacher training at the local level, should be applied. Nonetheless, the fact that the data was applied only to a selected region, and had a small size suggested the need to conduct studies in other underserved parts of the country. The study ended by recommending several policies that could improve both how accessible and high-quality ECCE was in South Punjab. Open-ended qualitative Google surveys collected responses from 14 respondents, public sector teachers and Assistant Education Officers (AEOs) who were working for ECCE in South Punjab. The findings indicated that a lack of proper policy implementation, resource scarcity, and poor teacher training were the major challenges for them. Supporting early learning required community as well as school-based action, yet poor parental involvement with socioeconomic gaps made educational outcomes difficult to achieve. The study further outlined the effective strategies that would assist in responding to such diversified development needs of younger learners, and it called for a focused intervention. The collaboration of governmental agencies, schools, and families was underlined as one strategy to enhance ECCE practices. As systematic gaps were revealed by this study, a contribution was made to the continuous debate on how early childhood education could be improved in disadvantaged regions.